FAKTOR-FAKTOR PENYEBAB STUNTING OBESITAS: NARRATIVE LITERATURE REVIEW - Prastiwi, Ratih Sakti; Qudriani, Meyliya; Umriaty; Nisa, Juhrotun (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKes Banyuwangi, 2023)
The problem of concurrent stunting and overweight (COS) in children has a low prevalence and is often overlooked. Children with COS are at increased risk for stunted growth and development and non-communicable diseases. Therefore, a preliminary review was conducted to identify the causes of COS in children under five years of age. A narrative review of the literature was conducted by searching the Scopus database using the keywords